Pengaruh Model Kulit Bumi terhadap Gelombang ScS dan ScS-ScS - Bagus Jaya Santosa (Jurnal Fisika dan Aplikasinya, 2009)
Intramuscular lipoma of the temporalis muscle is rare and may be difficult to distinguish from malignant lipomatous tumors when MRI shows atypical features. A 76-year-old woman presented with a progressively enlarging right temporal mass and a history of prior subcutaneous lipoma excision at the same site. Contrast-enhanced MRI revealed a large deep lipomatous mass with a heterogeneous nonadipose component involving the anterior temporalis muscle, raising concern for atypical lipomatous tumor/well-differentiated liposarcoma (ALT/WDL). The lesion was excised through a preauricular-based incision with temporal extension. Intraoperative frozen section suggested a benign lipomatous lesion, and final pathology confirmed intramuscular lipoma without lipoblasts or nuclear atypia. MDM2 immunostaining was negative, whereas CDK4 showed only focal nuclear staining. At 6 months, facial nerve function was preserved, and no clinical recurrence was evident. This case highlights that a large deep temporal intramuscular lipoma may mimic liposarcoma on MRI and that safe management requires integrated radiologic, intraoperative, and histopathologic correlation.